Ergonomical Assessment of Manually Operated Seed Drills for Farm Women - Singh, S P; Gite, L P; Agarwal, N (Journal of Agricultural Engineering, 2006)
A study on CIAE and PAU seed drills was conducted during rabi season in year 2003-04 at CIAE Bhopal in field for sowing wheat with farm women subjects to assess the physiological work load based on heart rate data during operation of both the seed drills. At a time two subjects were engaged for operation of each seed drill i.e. one for pulling and another for pushing/guiding the seed drill. Heart rate of each subject was recorded to evaluate both the seed drills. Both the seed drills were first ergonomically evaluated with women subjects. Based on the observations and feedback, both the seed drills were modified to suit 5th to 95th percentile of women’s height using anthropometrical information and re-evaluated ergonomically with women subjects in year 2004-05. The physiological workload in terms of work pulse was reduced by 23 % and 33.9 % in pulling and pushing modes of operation with the modified unit of CIAE seed drill as compared to its original unit. The corresponding values for modified PAU seed drill were 22.8 % and 9.0 %, respectively as compared to its original unit. The area covered with these units of CIAE and PAU seed drills was 430 mÂ²/h and 460 mÂ²/h, respectively at the speed of 2.5 km/h. The saving in terms of energy expenditure with modified units of CIAE and PAD seed drills was 27% and 24 %, respectively.